2010
DOI: 10.3109/09553000903419932
|View full text |Cite
|
Sign up to set email alerts
|

Growth of injected melanoma cells is suppressed by whole body exposure to specific spatial-temporal configurations of weak intensity magnetic fields

Abstract: Exposure to specific spatial-temporal regulated electromagnetic field configurations had potent effects on the growth of experimental tumours in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…We have adopted 4 h as the standard incubation time for the assay, absorbance was measured at 595 nm using a Biorad microtiter plates reader. When exposed for 5 consecutive days to a 50 Hz square wave at intensity of 5 µT, the cells showed a reduction of the growth rate (as measured by the tetrazolioum blue assay), compared to unexposed cells, and analogous to the aforementioned reports in the literature [64][65][66][67][68][69][70]; similarly, growth inhibition was observed also with exposure to the same frequency, at 245 µT.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We have adopted 4 h as the standard incubation time for the assay, absorbance was measured at 595 nm using a Biorad microtiter plates reader. When exposed for 5 consecutive days to a 50 Hz square wave at intensity of 5 µT, the cells showed a reduction of the growth rate (as measured by the tetrazolioum blue assay), compared to unexposed cells, and analogous to the aforementioned reports in the literature [64][65][66][67][68][69][70]; similarly, growth inhibition was observed also with exposure to the same frequency, at 245 µT.…”
Section: Discussionsupporting
confidence: 72%
“…3(b). This points to the benefits of a prolonged treatment strategy with low-level fields [63][64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, thermal radiation has been known to play a very important role for a very long time in the treatment of various diseases. On the other hand, Hu et al (2010) reported that the growth of injected melanoma cells was suppressed by a low intensity MF.…”
Section: Effect Of Magnetic Field On Enzyme Activitymentioning
confidence: 99%
“…This type of relationship reiterates the importance of the volume of the water to be affected as well as the pH with respect to the magneto-optic effects we have described. It is illustrative that at an intercellular pH of 6 there are approximately 3.15·10 5 free protons in an entire cell [36].…”
Section: Mechanisms Within the (Non-local) "Effective Zone"mentioning
confidence: 99%
“…Recently we [5] have found that the applications of weak (nT to μT range), physiologically patterned magnetic fields to animals in which tumors were induced resulted in a remarkable reduction of the size and expression of these malignant processes. The fields were applied in a temporal sequence between opposing pairs of solenoids in the X, Y, and Z planes followed by simultaneous generation in all planes (a "4-D" configuration) before the cycle repeated.…”
Section: Introductionmentioning
confidence: 99%